2017
DOI: 10.1002/ijc.30573
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin remodelling and DNA repair genes are frequently mutated in endometrioid endometrial carcinoma

Abstract: In developed countries, endometrial carcinoma is the most common cancer that affects the female genital tract. Endometrial carcinoma is divided into two main histological types, type I or endometrioid and type II or non-endometrioid, each of which have characteristic, although not exclusive, molecular alterations and mutational profiles. Nevertheless, information about the implication and relevance of some of these genes in this disease is lacking. We sought here to identify new recurrently mutated genes in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…45 KMT2 genes code for a homonymous family of methyltransferases, which are the effectors of histone H3 methylation, one of the epigenetic mechanisms regulating gene transcription. 46 In case of mutations, both JAK and KMT2 genes have been already described as potential drivers in MSI/dMMR tumours of other sites, 45 46 and we highlighted their potential involvement also in MSI/dMMR PDAC, further refining the knowledge on the genetic landscape of this tumour entity. Regarding survival of MSI/dMMR patients with PDAC, this systematic review revealed that there are no significant improvements in survival outcomes for this subgroup of patients.…”
Section: Discussionmentioning
confidence: 55%
“…45 KMT2 genes code for a homonymous family of methyltransferases, which are the effectors of histone H3 methylation, one of the epigenetic mechanisms regulating gene transcription. 46 In case of mutations, both JAK and KMT2 genes have been already described as potential drivers in MSI/dMMR tumours of other sites, 45 46 and we highlighted their potential involvement also in MSI/dMMR PDAC, further refining the knowledge on the genetic landscape of this tumour entity. Regarding survival of MSI/dMMR patients with PDAC, this systematic review revealed that there are no significant improvements in survival outcomes for this subgroup of patients.…”
Section: Discussionmentioning
confidence: 55%
“…revealed a synergistic role of hSET1 and NURF in regulating the USF‐bound barrier insulator that prevents erythroid genes from encroaching upon heterochromatin . Chromatin remodeling related genes ( KMT2D , KMT2C , SETD1B and BCOR ) is frequently mutated in endometrioid endometrial carcinoma . Collectively, we concluded that gene‐oriented ( SETD1B ) and pathway‐oriented networks are dependent and cooperative and require further investigation in PHNETs.…”
Section: Discussionmentioning
confidence: 81%
“…From clinical data we extracted the worst prognosis when both, ZEB1 and SETD1B were highly expressed whereas in the low/low group nearly all colorectal cancer patients survived the first 5 years after surgery. For endometrial carcinomas it was reported that for SETD1B mutant cases a higher myometrial invasion can be predicted 36 . In clear cell renal cell carcinomas SETD1B overexpression could discriminate metastatic from non-metastatic tumors 37 .…”
Section: Discussionmentioning
confidence: 99%